School Based Training Supports Continuous Professional Development in Kindergarten Teachers: Pelatihan Berbasis Sekolah Mendukung Keprofesian Berkelanjutan Guru Taman Kanak Kanak - Risna Purwanti; Marwan Marwan; Siraj Siraj; Munawar Munawar; Sari Rizki (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Continuing professional development is essential for strengthening teacher competence and sustaining educational quality in early childhood education. Specific Background: In Aceh Tamiang District, many kindergarten teachers still face limitations in early childhood learning methods, training access, and relevant professional development opportunities. Knowledge Gap: Empirical research remains limited on how a school-based training model is implemented for continuing professional development among kindergarten teachers in this local context. Aims: This study aimed to analyze the implementation of a school-based training model for the continuing professional development of kindergarten teachers in Aceh Tamiang District. Results: Using a qualitative case study involving 26 teachers, with data collected through observation, interviews, documentation, and focus group discussion, the study found that implementation was carried out systematically through planning, implementation, and evaluation stages. The process was supported by school-based management, teacher discipline, democratic principal leadership, educator commitment, professionalism, and adequate facilities. The study also identified obstacles, including limited understanding of school-based management among some education personnel, external policy intervention in school decision-making, limited mastery of teaching materials and teaching techniques, and uneven participation in evaluation meetings. Novelty: The study specifically examines school-based training and continuing professional development for kindergarten teachers in Aceh Tamiang by emphasizing local conditions, actual teacher needs, and institutional support. Implications: The findings indicate that school-based training can serve as a contextual and sustainable strategy for teacher professionalism when supported by participatory leadership, adequate resources, and stronger teacher capacity in learning management Highlights • Systematic stages covered program design, execution, and review.• Democratic leadership, staff discipline, and educator commitment sustained implementation.• Constraints involved managerial understanding, external policy pressure, teaching mastery, and meeting participation. KeywordsSchool Based Training; Continuing Professional Development; Kindergarten Teachers; School Based Management; Early Childhood Education